2022
DOI: 10.3390/ijerph192114486
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Research on the Treatment of Stormwater Contaminated by Disinfectants Using Recycled Materials—Hemp Fiber and Ceramzite

Abstract: Pollution caused by the use of disinfectants in public spaces is a relatively new form of environmental contamination. During the COVID-19 pandemic of 2020–2021, early research showed a sevenfold increase in the use of disinfectants to clean outdoor spaces and a corresponding increase in environmental pollution. Typically, after entering stormwater systems, disinfectants are carried to surface waters (e.g., rivers, seas and lakes) where they react with various elements to form harmful compounds. In the absence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
(22 reference statements)
0
6
0
Order By: Relevance
“…This research is ongoing. Initial data on the impact of chlorine-based disinfectants on stormwater pollution indicators [ 22 ] show that by increasing the amount of disinfectants, the stormwater pollution indicators change and residual chlorine concentrations are detected. This study is focused on the relationship of evaluation of the sodium hypochlorite with various microelements and its possible interaction and dependencies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This research is ongoing. Initial data on the impact of chlorine-based disinfectants on stormwater pollution indicators [ 22 ] show that by increasing the amount of disinfectants, the stormwater pollution indicators change and residual chlorine concentrations are detected. This study is focused on the relationship of evaluation of the sodium hypochlorite with various microelements and its possible interaction and dependencies.…”
Section: Resultsmentioning
confidence: 99%
“…Recent research reported on the relationship between disinfectant concentrations (sodium hypochlorite) and stormwater quality. Fluctuations in chlorine-based disinfectant concentrations have an immediate impact on stormwater pollution indicators, e.g., pH, conductivity, turbidity and colour [ 22 ], and also have an impact on aquatic microorganisms [ 23 ]. Studies have reported that the interaction of residual chlorine containing chemical substances (disinfectants) with organic and inorganic pollutants in water leads to the formation of disinfectant by-products: haloacetic acids, trihalomethanes, dibromochloromethane, bromodichloromethane, tribromethane, tribromoethane, dichloroacetonitrile, chloramines and other organic compounds [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The novelty of this research is that it analyzes the efficiency of waste materials and phytoremediation in the removal of residual chlorine from water. There is a lack of investigation on chlorine's impact on water environments and its retention processes from stormwater [32,16].The removal of residual chlorine depends on the following characteristics: the structure of filter material and the material's particle size, pore dimensions, pore volume and specific surface area [31]. The key hypothesis of the present research is that low-cost adsorbents and selected plants can be efficient in retaining residual chlorine and reducing its concentration in stormwater.…”
Section: Methodsmentioning
confidence: 93%
“…The increased use of chlorine-based disinfectants and residual chlorine toxicity in water bodies have increased our need to analyze residual chlorine's impact on water environments and provide possible methods and materials for its reduction. Previous studies have revealed that stormwater contaminated by chlorine and chlorine compounds can be treated using natural sorbents [31]. The novelty of this research is that it analyzes the efficiency of waste materials and phytoremediation in the removal of residual chlorine from water.…”
Section: Introductionmentioning
confidence: 99%
“…The novelty of this research is to analyze wasted materials and phytoremediation efficiency of residual chlorine removal. The retain of residual chlorine depends on the following characteristics: structure of filter material, material's particle size, pore dimensions, pore volume and specific surface area [32]. Present research was conducted with the following specific objectives: (1) to evaluate the efficiency of different low cost and recyclable filter materials to retain residual chlorine; (2) to test plants efficiency to reduce residual chlorine concentration by phytoremediation; and (3) to provide with findings on materials could be used in green infrastructure in order to reuse stormwater.…”
Section: Introductionmentioning
confidence: 99%